Endoparasites new to the Neotropical freshwater turtle, Mesoclemmys vanderhaegei (Bour 1973) (Testudines, Chelidae), from central Brazil. - Avila, Robson W.; Brito, Elizangela S.; Barrella, Thomaz H.; Strussmann, Christine; Silva, Reinaldo J. (My University, 2010)
Information on endoparasites infecting Neotropical turtles is scarce. The present paper reports the occurrence of endoparasites in three adult individuals of Vanderhaege's Toad-Headed Turtle (Mesoclemmys vanderhaegei). The records include an undescribed nematode species in the genus Spiroxys, not previously reported for the family Chelidae, and the first South American record of a monogenetic trematode of the genus Neopolystoma.